TREATMENT OF INTERNAL CAROTID ANEURYSMS USING PIPELINE EMBOLIZATION DEVICES: MEASURING THE RADIATION DOSE OF THE PATIENT AND DETERMINING THE FACTORS AFFECTING IT. Issue 3 (10th January 2020) - Kawauchi, Satoru; Chida, Koichi; Moritake, Takashi; Hamada, Yusuke; Matsumaru, Yuji; Tsuruta, Wataro; Sato, Masayuki; Hosoo, Hisayuki; Sun, Lue
Abstract: The purpose of this study was to measure the peak skin dose (PSD) and bilateral lens doses using radiophotoluminescence glass dosimeters and to determine the factors influencing the radiation dose in cases of cerebral aneurysm treated with pipeline embolization devices (PEDs). The cumulative dose, PSD and right and left lens doses were 3818.1 ± 1604.6, 1880.0 ± 723.0, 124.8 ± 49.2 and 180.7 ± 124.8 mGy, respectively. Using multivariate analysis, body mass index ( p < 0.01; odds ratio (OR) = 1.806; 95% confidence interval (CI) = 1.007–3.238) and deployment time of PED ( p < 0.05; OR = 1.107; 95% CI = 1.001–1.224) were found to be the independent predictors of PSD exceeding 2 Gy. Measures such as collimation of the radiation field and optimization of radiation dose should be taken to reduce the radiation to the patient.